Strategizing: Opening New Avenues in Latin-America. A Systematic Literature Review (2019)
Strategizing is a research field devoid of epistemological, theoretical and methodological unity. Instead of seeing it as a disadvantage, we show how this plurality boosts the convergence of different points of view in the practice turn of strategy that challenges its conventional perspective. Through this systematic literature review we detected research opportunities in Latin-America, as well as in the categories of Strategizing such as practices and practitioners. In the first category, we suggest trust as a suitable concept for research on the social nature of practices. And in the second category, customers claim further attention as relevant actors in the creating-delivering-capturing value cycle of the business level strategy.